Precarious spaces: intersections of gendered identity and violence in Zimbabwean literature - Chando, Aaron (University of the Witwatersrand, Johannesburg, 2022)
This thesis examines ways in which selected Zimbabwean literary works expand understandings of the cultural production and deconstruction of precarity. It seeks to advance the claim that a cross-section of Zimbabwean writers espouses a ‘precarious aesthetic’ to reimagine the nation by deconstructing cultural practices that produce and sustain precarity. I postulate that precarity is ideologically produced at the intersections of gendered identities and institutionalised forms of violence, such as ethnonationalism, heteropatriarchal policing, ableism, homophobia, and misogyny, where notional understandings of masculinity and femininity become central to the politics of (un)belonging. I draw on premises from precarity, gendered identities, and intersectionality studies to make a case for a space-bound understanding of precarity that recognises Zimbabwean textual nuances and environmental specificities. By deploying Western-based theorisations of precarity to address dynamics of disempowerment in a Zimbabwean context, I seek to demonstrate that precarity discourses are in a constant process of becoming and to expand discursive space on a subject that has been predominantly approached through tropes of drought and hunger. A cross-cutting premise in precarity studies is that the experience of marginalisation promotes radical thinking, which enables victims to weaponise their condition. This underwrites my assumption that all marginalising impulses leave spaces for pushback, strategic surrender, and self-affirmation. Therefore, throughout the five core chapters of the thesis, I adopt a close reading strategy to offer context-specific evaluations of refusal politics undertaken by precarious subjects in different sites of displacement. I propose that exploring overlaps among marginalising ideologies and pushback mechanisms can unravel new insights about the political function of vulnerability and bring forth a new grammar with which to talk about precarity. Overall, I argue that the literary front constitutes a site of reinvention where precarious subjects are radically written into existence and where diversity and difference are recast as indices of social hygiene.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in English Studies, to the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2022.
Keywords: Precarity; Gendered identity; Difference; Cultural disablement; Violence; Radical vulnerability; Minoritization; Intersections; UCTD; SDG-4: Quality education